Analisis Parameter Kinerja Mesin Granulator dalam Proses Produksi Pupuk NPK - Nurlianna Tarigan; Karti Karti; Nelson Silitonga; Immanuel Yorlando Simanjuntak (CV. IRA PUBLISHING, 2026)
The process of making NPK fertilizer in granular form is greatly influenced by the performance of the granulator machine used. The granulator plays an important role in producing fertilizer granules with a consistent size, hardness, and homogeneity to meet quality standards and facilitate distribution and field application. This study aims to analyze the performance parameters that affect the efficiency of granule formation in NPK fertilizer and the influence of the granulator on the granule formation process. The research method involved direct observation of the production process and testing the quality of the granules, including particle size distribution, mechanical hardness, and frictional resistance. The results of the study show that, at a granulator rotation speed of 21 rpm and a torque of 28.5 N · m, the NPK fertilizer manufacturing process produces an effective capacity of 24,384 kg/hour. And shows that the more optimal the control of the work parameter settings, the higher the process efficiency and the quality of the NPK fertilizer granules produced.